Kleinigkeiten im Kyklops des Euripides - Holzhausen, Jens (Hyperboreus, 2022)
The essay is concerned with certain passages of Euripides’ Cyclops. In lines 182–185 the satyrs picture Helen as a woman who lets herself be seduced by a Paris who is everything but a real man. Line 222 is to be seen as a response to Aristophanes’ mockery. In 226–227 there is no need to modify the text of ms. L. Line 231 is not to be taken as evidence that the Cyclops sees himself as a god. In 235 κατὰ τὸν ὀμφαλὸν μέσον is to be read after Scaliger. In 241–242 the expression κοπίδας μαχαίρας is to be understood as a genitive connection. In 245 ms. L’s ἔδοντος is to be accepted. In 268 κακοί is to be interpreted as predicative. In 306–307, ἀλόχους τ’ ἀνάνδρους γραῦς τ’ ἄπαιδας … πολιούς τε πατέρας, and in 349, γνώμην … ἀλίμενόν τε καρδίαν, one has to recognise a daring image in which the negation is reversed. The image of Silenus trapped like a flapping bird hanging on a lime-twig (432–434) only carries meaning if ἀποκερδαίνω is interpreted as having a conative sense. For the corrupt lines 439 f. a new reading is proposed, according to which the satyrs view the wine as a lost spouse. For the difficult and much-discussed passage 469–471 a simple solution is sought: for the blinding of Polyphemus the satyrs want to touch the burning log, as, when making a burnt offering, one might touch the remaining logs of a fire after having quenched the flames with wine. In the corrupt line 593 the conjecture ὠθεῖν καπνῶν (part. praes. act.) is suggested. In 617 the transmitted μαινόμενος is to be retained. Lines 632–634 are to be assigned to Odysseus. Line 674 is not corrupt: it contains the quick-witted reply of Polyphemus to the satyrs’ inane question: “You are not blind then?” In 694 Dobree’s conjecture καλῶς for the transmitted κακῶς is to be accepted.